Interpersonal violence in Europe: markers of prevalence and effective prevention programmes. (1st March 2011) - Minicuci, N; Andreotti, A; Rigby, M; Alexander, D; Vincenten, J; Bellis, M; Perkins, C; Hughes, K; Perttu, S; Saavola, T; Geldschlger, H; Zurrilla, M; et al.
Abstract : In the WHO European Region, 73 000 people were killed by interpersonal violence in 2002, and homicide represents the third leading cause of death after road traffic and suicide. Information on deaths is relatively easy to collect but these are just the tip of the iceberg: psychological, physical, sexual damage and neglect are not captured by routine data. To address this, the general objectives of the PHASE (Public Health Actions for a Safer Europe) project are to enhance injury data exchange in the Member States and to reinforce current health-sector related networks; in particular WP 6 addresses the theme of interpersonal violence. Four focus intervention areas have been identified: child, youth, intimate partners and elderly and four teams of European experts in collaboration with WHO National Focal Points on injury and violence prevention have identified and collected information on: (a) Country profile indicators; (b) Markers of prevalence; (c) Characteristics of violent behaviour; (d) National strategies, prevention programmes and services; (e) Legislation; (f) Reporting Systems; (g) Cost Analysis in the 27 European member states. These domains aimed to describe the magnitude of violence, understand which factors increase the risk for violent victimisation and perpetration, identify which type of programmes are effective and how legislation acts in this respect. The presentation will focus on the methodology adopted; discuss gaps and deficiencies in available information; present epidemiological findings and meta-analysis results. Intervention programmes and strategies that have been implemented and shown effectiveness in preventing violence will also be presented.